The Influence of Digital Media Use on Sales Level of Culinary Package Product Among Female Entrepreneur - Qurata Ayuni; Hafied Cangara; Arianto Arianto (BPSDMP Kominfo Manado, 2019)
The development of new media has changed the pattern of communication and market interaction. Cyberspace is a modern business model that provides space for buying and selling transactions. It requires entrepreneur to master technology, including womanpreneur. Its appearance is triggered by the facilities and opportunities of social media technology. This quantitative-descriptive research focus on the positive influence of digital media to increase the sales of specialty food products among womanpreneur in Makassar. The number of sample is 139 respondents, who are micro entrepreneurs and has been established at least six months and used social media were Facebook or Instagram. The independent variable is digital media utilization (X), the control variable is marketing mix (Z), and the dependent variable is level of sales (Y). The results of this research obtained that the variable digital media utilization (X) and marketing mix (Z) has an influence on the level of sales (Y). H1 is accepted whereas H0 is rejected, stating that digital media (e-marketing) utilizatin is a positive influence on increasing the sales of specialty food products among womanpreneurs in Makassar.